TANGGUNG JAWAB NOTARIS ATAS AKTA PERJANJIAN PERKAWINAN YANG DIBATALKAN OLEH PUTUSAN MAHKAMAH AGUNG (STUDI PADA PUTUSAN MAHKAMAH AGUNG NOMOR 598 PK/PDT/2016) - Edric Victori; Gunawan Djajaputra (Fakultas Hukum Universitas Tarumanagara, 2021)
A marriage is a legal act if it is carried out according to the provisions of the law that apply. Married couples make marriage agreements before they legalize their marriage, which usually concerns the arrangement of marital property and made to anticipate problems that might arise when the marriage ends according to the law. Law 2 of 2014 concerning the Position of Notary Public, the notary is authorized to make authentic deeds regarding all actions, agreements and stipulations required by statutory regulations and desired by those concerned to be stated in authentic deeds relating to the marriage agreement deed made by the Notary. There is a case about the cancellation of the marriage agreement deed in the Supreme Court Decision Number 598 PK / Pdt / 2016. The result of the research is legal consequences of marriage agreement deeds that are not made in front of a marriage legislator, based on Article 29 paragraph 1 of Law Number 1 of 1974 concerning Marriage and article 147 of the Civil Code, if the marriage agreement is not registered. For married couples who have made a marriage agreement but did not register it to the marriage legislator, the agreement remains binding on both parties, but for third parties, in this case the Notary, if the marriage agreement is not registered, the legal consequence is that the marriage agreement has no power binding law.